Paradoxically developed optochiasmatic tuberculoma and tuberculous lymphadenitis: A case report with 18-month follow up by MRI - Kalkan, Ahmet; Serhatlioglu, Selami; Ozden, Mehmet; Denk, Affan; Demirdag, Kutbettin; Yilmaz, Turgut; Kilic, Suleyman Sirri (Lippincott Williams & Wilkins, 2006)
We report the first case of extracranial tuberculous lymphadenitis which paradoxically developed during treatment of intracranial tuberculoma. Our patient, a 15-year-old girl who initially presented with meningitis and intracranial tuberculomas, developed extracranial tuberculomas during treatment for central nervous system tuberculosis. She was followed clinically with cerebrospinal fluid (CSF) studies and magnetic resonance imaging (MRI) at three monthly intervals. Within 18 months of specific antituberculous treatment, the patient had fully recovered. The course and response to therapy are discussed in light of the current literature.
Keywords: tuberculous lymphadenitis; extracranial; intracranial optochiasmatic tuberculoma